2022
DOI: 10.3390/bioengineering9080333
|View full text |Cite
|
Sign up to set email alerts
|

Soccer Scoring Techniques—A Biomechanical Re-Conception of Time and Space for Innovations in Soccer Research and Coaching

Abstract: Background: Scientifically, both temporal and spatial variables must be examined when developing programs for training various soccer scoring techniques (SSTs). Unfortunately, previous studies on soccer goals have overwhelmingly focused on the development of goal-scoring opportunities or game analysis in elite soccer, leaving the consideration of player-centered temporal-spatial aspects of SSTs mostly neglected. Consequently, there is a scientific gap in the current scoring-opportunity identification and a dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…The study revealed that scoring with a one-touch shot accounted for 69.3% of goals, setting up a shot resulted in only 17.9% of goals, and a shot after individual dribbling had the lowest percentage (12.8%). A recent study [5] unveiled similar results: 56.8% for zeropossession shots, 13.6% for one-possession shots, and 29.6% for more-than-two-possession shots. These results suggest that, with an increase of ball-contact times, the scoring chance is continuously decreased.…”
Section: Temporal Factors Related To Shooting Effectivenessmentioning
confidence: 53%
See 4 more Smart Citations
“…The study revealed that scoring with a one-touch shot accounted for 69.3% of goals, setting up a shot resulted in only 17.9% of goals, and a shot after individual dribbling had the lowest percentage (12.8%). A recent study [5] unveiled similar results: 56.8% for zeropossession shots, 13.6% for one-possession shots, and 29.6% for more-than-two-possession shots. These results suggest that, with an increase of ball-contact times, the scoring chance is continuously decreased.…”
Section: Temporal Factors Related To Shooting Effectivenessmentioning
confidence: 53%
“…Hence, it is logical for both researchers and practitioners to explore all means that could increase the chance and effectiveness of shots taken. Until now, practitioners have unearthed numerous SSTs that can be applied in various game situations; in contrast, scientific investigations (especially biomechanical studies) have only been conducted in a few of the SSTs seen in the game [3,5]. This scenario has resulted in the lack of science-based SST training in current soccer practice.…”
Section: Identification Of Sstsmentioning
confidence: 99%
See 3 more Smart Citations